PENGARUH PROMOSI PENJUALAN ONLINE DAN OFFLINE TERHADAP JUMLAH SISWA DI GOLDEN ENGLISH TAHUN 2023 - Andini, Reyta Pitri (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to investigate the influence of online and offline sales promotions on the number of students enrolling at Golden English in 2023. The research method used was a survey, collecting data from 46 respondents who were potential students of Golden English. The collected data was then analyzed using multiple regression analysis techniques to examine the relationship between the sales promotion variables (online and offline) and the number of student enrollments. The results of the study show that both online and offline sales promotions have a significant positive impact on the number of students enrolling at Golden English. This means that the more intensive and effective the sales promotions are, both online and offline, the greater the likelihood that potential students will be interested in enrolling at this institution.